Identification of indole-3-acetic acid as an important hormone in post– pollination of Dendrobium orchids and interaction of other hormones - Netlak, Petcharat; Imsabai, Wachiraya; Munné-Bosch, Sergi; Leethiti, Preeyapon; Doorn, Wouter G. van (Agriculture and Natural Resources, 2022)
Importance of the work: A ‘pollen hormone’ in Dendrobium pollinia has been reported for over a century but the specific nature of such a compound or compounds has not been proven. Objectives: This study investigated the ‘pollen hormone’ in pollinia of Dendrobium orchid cultivars that display contrasting post-pollination phenomena. Materials & Methods: The aqueous extract of pollinia of two Dendrobium cultivars was analyzed using gas chromatography-mass spectrometry. Hormonal profiles of cytokinins (CKs), auxin (IAA), gibberellic acids (GAs), abscisic acid (ABA), jasmonic acid (JA), salicylic acid (SA), and 1-aminocyclopropane-1-carboxylic acid (ACC) were analyzed using ultra-high-performance liquid chromatography-tandem mass spectrometry. The effects of the plant hormones on post-pollination of Dendrobium cv. Miss Teen was studied. Results: An aqueous extract of pollinia showed a relatively high indole-3-acetic acid (IAA) concentration in Sakura (exhibits post pollination) was about 4.28 ng/μL, whereas no IAA concentration was detected in Miss Teen (fails to show post pollination). The IAA in the whole pollinia of Dendrobium cultivars showing post-pollination phenomena was an average of 227,070.25 ng/g pollen and higher concentrations than those cultivars that do not. Post-pollination effects were associated with elevated concentrations of IAA, ABA, SA, and gibberellins; however, no correlations were observed with JA and CKs. Dendrobium cv. Miss Teen, when treated with IAA singly or in combination with IAA plus ABA, SA, or GAs, induced the same post-pollination symptoms as found in a pollinated flower, while flowers treated with ACC did not induce a post-pollination response. Main finding: The auxin presence in the pollinia of Dendrobium was associated with the occurrence of post-pollination events. These data strongly suggested that the main ‘pollen hormone’ in Dendrobium flowers was likely IAA and that it interacts with ABA, SA, and some GAs.